Análise numérica da combustão em um motor de ignição por centelha com pré-câmaras de diferentes geometrias operado com etanol - Miguel Humberto Barrientos Sandoval (2019)
The increase of pollutant emissions demands the industries to find new technologies focused on the maximum exploitation of natural resources with reduction of contamination levels. In the automotive sector, despite not being an modern technology, the use of engines with ignition system of pre-chamber is projected to be one of the most suitable to generate power reducing contamination levels and fuel consumption, since the system allows significant gains in the combustion parameters that allow the use of poor blends in the engine. The ignition system with pre-chamber consists on the setup of a small additional combustion chamber, or pre-chamber, interconnected through connection channels with the main chamber. In this system, the combustion starts from an electrical spark in the pre-chamber, where both pressure and temperature rise, which generates flame jets, which are directed to the main chamber. In the ignition system with pre-chamber, besides the proportion of air/fuel, its geometry is one of the most important parameters, once it directly influences on the combustion characteristics and on the gas emission of the engine. In this work it is minutely analyzed the performance of an internal combustion engine, equipped with an ignition system with pre-chamber operating with homogeneous load, varying the pre-chambers internal volume and the diameter, quantity and arrangement of the interconnection channels. The results indicate that the increase of internal volume of the pre-chamber is the parameter that influences the most the combustion process. On the other hand, the proper sizing, distribution and setup of the interconnected channels provide small gains in terms of the combustion efficiency and allow a proper distribution of jets in the main chamber.